Estimasi Biaya Pemeliharaan Bangunan Berdasarkan Pedoman Pemeliharaan Dan Perawatan Bangunan Gedung (Permen Nomor: 24/PRT/M/2008) (Studi Kasus Gedung Perpustakaan Wilayah Soeman H,S Pekanbaru) - Riandika Nugraha; Rian Trikomara Iriana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Building maintenance is necessary to keep buildings viable and livable, not least Soeman H.S library of Pekanbaru. This maintenance should be continuos, so it can be reduce the damage to the building. It is necessary for the proper maintenance strategy based on state laws, Permen No:24/PRT/M/2008, to obtain predictions maintenance costs required by the building. In analyzing the cost of repairs used approximate estimate method wich is the highest unit price per m2 rise buildings.Based on the analysis, the repair costs is Rp. 300,484,825.10,-, the percentage of damage is 0.52 %. Soeman H.S library damage is still considered minor damage, wich is below the percentage of damage required, ie 30 %. While the maintenance costs is Rp. 1,881,364,861.11,- and predicted to increase annually.Keywords: approximate estimate, repair costs, maintenance costs, building maintenance